Influent Pelajaran Prakarya Dan Kewirausahaan Terhadap Minat Berwirausaha Siswa Di SMEA Taqwa Belitang Oku Timur - Andi Andriyansyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Interest in entrepreneurship is the desire or interest to create business opportunities without being afraid of the risks that will occur, and having an achievement motive in entrepreneurship. The research data was collected using the pretest and posttest questionnaire methods. Where is the pretest questionnaire method to see how much students are interested in entrepreneurship before getting the subject of crafts and entrepreneurship and posttest questionnaires to see how much students are interested in entrepreneurship after getting the craft and entrepreneurship subjects. This research uses descriptive quantitative data with a certain percentage using the Azwar scale formula, so that it can determine the percentage and can be described with words or sentences to draw conclusions.